Arqueologia e história na terra dos bugres: em busca da visibilidade indígena na região de Cruz Alta - RS - Almeida, Fernando Silva de (2012)
The objective of this study is to perform an investigation, based on ethno-history study, about the presence of indigenous groups living since pre-colonial periods in the region of Cruz Alta. Are introduced archaeological and documentary information about the presence of groups Guaranis and Kaingangues occupying the actual territory of the city. In addition, are evaluated some factors which led the indigenous communities to be disregarded in historical discourses. To achieve this goal, surveys were done about the colonialism literature, the role of archeology as a reproducer of this ideology, the discourse about indigenous groups in national projects by brazilians intellectuals in the nineteenth and twentieth centuries and some aspects of the identity discourses about indigenous groups in the state of Rio Grande do Sul and also in the county where this research takes place: Cruz Alta. Is evident that there are many more stories that can be counted by different social actors, and the archaeological sites existing in the region still not are depicted like an archeological heritage of society, considering the lack of knowledge about the pre-colonial materiality and indigenous history. Thus, through historical research, it is understood that other visions of the past can be discussed, contributing to the construction of multiple cultural identities.